Association of blood glucose levels and body mass index with menstrual cycle patterns among female medical students at Universitas Syiah Kuala - Annisa Salsabila Br. Manurung; Husnah Husnah; Nora Sovira; Desi Maghfirah; Cut Rika Maharani (Indonesian Nutrition Association, 2026)
Background: Menstrual cycle disorders are prevalent among women of reproductive age and may be influenced by nutritional and metabolic factors. Body mass index (BMI) and blood glucose levels play important roles in hormonal regulation and reproductive function. Objective: This study examined the association between blood glucose levels and body mass index with menstrual cycle patterns among female medical students at Universitas Syiah Kuala. Methods: An analytical cross-sectional study was conducted among 249 female medical students from the 2022–2024 cohorts using quota sampling. Data were collected from 8 - 16 September 2025. Menstrual cycle patterns were assessed using an online menstrual diary based on International Federation of Gynecology and Obstetrics criteria. Blood glucose levels were measured using random blood glucose testing, and BMI was calculated from measured weight and height. Associations were analyzed using Spearman rank correlation and ordinal logistic regression. Results: Most participants had normal blood glucose levels (61.8%) and normal BMI (44.6%). Normal menstrual cycles were reported by 57% of participants. Blood glucose levels were significantly associated with menstrual cycle patterns (p = 0.022; rₛ = 0.145). BMI was also significantly associated with menstrual cycle patterns (p = 0.038; rₛ = 0.132). The correlation coefficients indicated weak positive relationships between blood glucose levels and BMI with menstrual cycle. Multivariate analysis showed that BMI (OR = 5.06) had a stronger association with menstrual cycle disturbances than blood glucose levels (OR = 4.66). Conclusion: Blood glucose levels and body mass index are significantly associated with menstrual cycle patterns, with BMI identified as the dominant factor. Maintaining optimal nutritional and metabolic status may support menstrual health in young women.